Anting Emas di Jungur Babi: Analisa Penggunaan Kiasan terhadap Pola Perkataan Item-Evaluasi Menurut Amsal 11:22 - Aska Aprilano Pattinaja; Hemy Bernard Warikry; Farel Yosua Sualang (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2024)
Proverbs 11:22 is a unique section of Solomon's Proverbs because it contains a metaphor comparing an immoral woman to a gold ring on a pig's jaw. The debate about this verse is the misinterpretation of this verse as anti-feminist or misogynistic, which implies a misunderstanding of the intended context. There is a gap in the previous research which only discusses the study of the meaning and its embelamatical implications, thus not answering the need for a comprehensive explanation of the figurative context and meaning of the verse. Therefore, to provide the correct interpretation and perspective, this research is conducted in discussing the figurative meaning and analyzing the item-evaluation speech pattern, so as to interpret the figurative meaning of